MODERN VIEW TO OPTIMIZE THE DIAGNOSIS OF THE COURSE OF PARKINSON’S DISEASE - Daminova, H.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Parkinsonism is one of the most significant problems in clinical neurology, both due to its high prevalence in the world’s populations and due to the significant disability of patients. The paper analyzes the diagnosis of Parkinson’s disease (as well as other neurodegenerative diseases) at the prodromal stage. An overview of the methods of preclinical and early clinical diagnosis of PD shows that the study of the prodromic markers and the criteria of the Premotor Phase of PD will allow in the future to significantly change the course of the disease using neuroprotective therapy at the stage preceding the death of a significant number of dopaminergic neurons of the Black Substance.